Duration, course and caregiver burden of croup in children: two observational cohorts - David W Johnson; Alberto Nettel-Aguirre; Candice Leigh Bjornson; Janielee Williamson (BMJ Open)
Objectives Although croup is a common respiratory illness, there is little published regarding symptom course. We aimed to assess symptom progression and caregiver burden, and whether age, sex or season and initial severity of disease are associated with symptom duration.Design, setting and participants We conducted a secondary analysis of two Canadian prospective cohorts of children 0–16 years old diagnosed with croup; one recruited from a paediatric emergency department (ED) (307 children) between November 1999 and March 2000, and the other from 26 general EDs (1214 children) between September 2002 and April 2006. Baseline data included age, sex, season, corticosteroid treatment and clinical severity score based on the presence or absence of a barky cough, stridor at rest or with agitation and chest wall indrawing (mild, moderate or severe). For both cohorts, the child’s primary caregiver was telephoned daily to collect symptom progression and psychosocial data (caregiver stress, lost sleep and work) until the child was symptom-free for over 24 hours.Results The paediatric and general ED cohorts are reported separately; croup symptoms peaked at initial ED presentation for 96% and 77%, respectively. The longest-lived symptom was a barky cough, resolving by 34 and 47 hours for 50%, and 78 and 119 hours for 90% of children, respectively. Neither sex nor severity at presentation were significantly associated with symptom duration in either cohort. Season of illness was associated in both; age was associated in the general but not the paediatric ED cohort. The primary caregiver lost a mean (SD) of 4.1 (4.9) and 2.8 (4.7) hours of sleep during the illness.Conclusions Most children with croup presented for care at the peak of symptom severity. Symptoms resolved for half of the children in 1.5–2 days and for 90% in 3–5 days after presentation. Caregivers experienced a significant loss of sleep.